Negative electrode additive as well as preparation method and application thereof

By introducing high conductivity and sodium ions-rich negative electrode additives into the hard carbon negative electrode, the problems of high consumption and low stability of hard carbon materials in sodium ion batteries are solved, and a sodium ion battery with high capacity, high Coulomb efficiency and excellent cycling stability are achieved.

CN119674076AActive Publication Date: 2025-03-21JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411807187.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-21
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

As the anode material of sodium ion batteries, hard carbon has disordered structure that leads to high consumption of active sodium, low initial Coulomb efficiency and cycling stability, and low conductivity limit rate performance. Existing improved methods such as pre-sodiumization, surface coating and electrolyte optimization have problems of complex operation, high cost or poor cycle stability.

Method used

Highly conductive and sodium ions-rich negative electrode additives are prepared by self-polymerization of conductive polymer monomers in the presence of organic sodium salts, and composite negative electrode materials are prepared by mixing them with hard carbon by ball mills to improve conductivity and compensate for Na+ loss during the formation of SEI film.

Benefits of technology

The capacity of sodium ion batteries, first-time Coulomb efficiency and cycle stability are improved, the side reaction between hard carbon and electrolyte is reduced, and the irreversible capacity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674076A_ABST
    Figure CN119674076A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode additive and a preparation method and application thereof, and the preparation method of the negative electrode additive comprises the following steps: (1) adding a conductive polymer monomer and an organic sodium salt into a solvent, and uniformly mixing to obtain a mixture; and (2) adding an initiator solution into the mixture prepared in the step (1), stirring, filtering, washing and drying to obtain the negative electrode additive. The negative electrode additive prepared by the preparation method is rich in sodium ions and has good conductivity, and a composite material formed by mixing the negative electrode additive with hard carbon can be used as a negative electrode material for constructing a sodium ion battery, so that the capacity and the first coulombic efficiency of the sodium ion battery are effectively improved; and the problem of fast capacity fading of the hard carbon negative electrode in the cycle process can be effectively relieved, so that the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode additive and a preparation method and application thereof. Background Art

[0002] As a substitute for lithium-ion batteries (LIBs), sodium-ion batteries (SIBs) have shown unprecedented potential due to their abundant resources and high cost-effectiveness, especially in electric vehicles (EVs) and large-scale power systems. Hard carbon has been given priority as a candidate material for the anode of commercial SIBs due to its low cost, large carbon interlayer spacing, and appropriate redox potential. The disordered crystal arrangement and large interlayer distance of hard carbon provide space for storing a large amount of charge, but this disordered structure will cause it to consume a large amount of active sodium during the charge and discharge process, forming a SEI film that causes irreversible consumption, resulting in low initial coulombic efficiency (ICE) and poor cycle stability. At the same time, the poor electrical conductivity of hard carbon itself will further limit its rate performance and cycle performance, affecting its commercial application.

[0003] At present, the methods for improving the first effect of hard carbon mainly include pre-sodiumization, carbon material surface coating, electrolyte optimization and other means, but these methods still have limitations. Surface coating generally requires the deposition of an inert layer or carbon layer on the carbon surface by atomic layer deposition technology to reduce the surface activity. This method requires complex operation processes and equipment; electrolyte regulation. It is currently found that ether electrolytes have higher first effects, but poor cycle stability; pre-sodiumization is to introduce exogenous sodium into the battery system in a suitable manner and form, by introducing excess Na + Forming a stable SEI can simultaneously compensate for Na + The loss of electrolyte and the continuous decomposition of electrolyte are prevented. The current pre-sodiumization technology mainly adopts the pre-sodiumization at the electrode level. The pre-sodiumization process at the electrode level requires the addition of pre-sodiumization process steps and corresponding equipment and environmental space, which greatly increases the manufacturing time cost, equipment investment cost, etc., which is not conducive to commercial promotion. Therefore, it is still necessary to develop green, simple, effective and controllable methods to improve the performance of hard carbon materials. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a negative electrode additive and a preparation method and application thereof. A negative electrode additive with high conductivity and rich in sodium ions is prepared by self-polymerization of a conductive polymer monomer in the presence of an organic sodium salt; the negative electrode additive and hard carbon can be mixed by ball milling to prepare a composite negative electrode material. Compared with the hard carbon negative electrode, the composite negative electrode material containing the negative electrode additive can improve the conductivity of the negative electrode and compensate for the Na ions in the process of forming the negative electrode SEI film. + The loss is reduced, so that the sodium ion battery constructed with the composite negative electrode material has high capacity, high first coulombic efficiency and excellent cycle stability.

[0005] Specifically, the following technical solutions are provided:

[0006] The first aspect of the present invention provides a method for preparing a negative electrode additive, comprising the following steps:

[0007] (1) adding a conductive polymer monomer and an organic sodium salt into a solvent and mixing them uniformly to obtain a mixture;

[0008] (2) Adding an initiator solution to the mixture prepared in step (1), stirring the mixture, filtering the mixture, and drying the mixture to obtain the negative electrode additive.

[0009] Furthermore, in step (1), the conductive polymer monomer is aniline, pyrrole or thiophene.

[0010] Furthermore, in step (1), the organic sodium salt is selected from one or more of disodium hexamethylenetetraacetic acid, disodium glutarate, sodium benzoate, and disodium phthalate.

[0011] Furthermore, in step (1), the solvent is selected from one or more of water, ethanol, ethylene glycol, N-methylpyrrolidone, dimethylformamide, and toluene.

[0012] Furthermore, in step (1), the mass ratio of the conductive polymer monomer to the organic sodium salt is (1-3):1, such as 1:1, 2:1, 3:1, etc., including but not limited to the mass ratios listed above.

[0013] Furthermore, in step (2), the initiator solution is obtained by dissolving an initiator in a solvent. Preferably, the initiator is ammonium persulfate, and the solvent contains water.

[0014] Furthermore, in step (2), the ratio of the molar amount of the conductive polymer monomer in the mixture to the molar amount of the initiator in the initiator solution is 1:(1-4), for example 1:1, 1:2, 1:3, 1:4, etc., including but not limited to the ratios listed above.

[0015] Furthermore, in step (2), the initiator solution is added dropwise to the mixture, and during the adding process: the temperature is preferably -15-5°C, and the adding time is preferably 1-24h.

[0016] Furthermore, in step (2), the stirring treatment time is preferably 2-4 hours.

[0017] Furthermore, in step (2), the drying temperature is preferably 80-100° C., and the drying time is preferably 4-5 h.

[0018] Furthermore, the preparation method further comprises the step of washing the filtered product; the washing solvent is preferably ethanol and / or water.

[0019] The second aspect of the present invention provides a negative electrode additive prepared by the preparation method described in the first aspect.

[0020] The third aspect of the present invention provides a composite negative electrode material, comprising hard carbon and the negative electrode additive described in the second aspect.

[0021] Furthermore, the hard carbon is prepared by the following preparation method, which specifically comprises the following steps:

[0022] S1, calcining the carbon source for the first time under a protective atmosphere to obtain a carbon precursor;

[0023] S2, calcining the carbon precursor for a second time in the presence of a gas phase pore former, and then calcining the carbon precursor for a third time in a protective atmosphere, and washing the product with acid and drying the product to obtain the hard carbon.

[0024] Furthermore, in S1, the carbon source can be selected from one or more of polymer materials, coal materials and biomass materials, wherein the polymer materials include phenolic resin, polytetrafluoroethylene, epoxy resin, furan resin, etc., the coal materials include anthracite, bituminous coal, lignite, coal tar, etc., and the biomass materials include sucrose, glucose, starch, coconut shell, sugarcane, poplar, etc.

[0025] Furthermore, the protective atmosphere includes one or more of nitrogen, argon, helium, and krypton.

[0026] Furthermore, in S1, the temperature of the first calcination treatment is 450-550°C, and the time of the first calcination treatment is 3-5h.

[0027] Furthermore, in S2, the gas-phase pore-forming agent includes one or more of carbon dioxide, oxygen, air, and water vapor; preferably, the gas-phase pore-forming agent is introduced during the heat preservation stage of the second calcination treatment, and the gas flow rate of the gas-phase pore-forming agent is preferably 10-100 L / min.

[0028] Furthermore, in S2, the temperature of the second calcination treatment is 800-900°C, and the time of the second calcination treatment is 1-10h.

[0029] Furthermore, in S2, the temperature of the third calcination treatment is 1100-1500° C., and the time of the third calcination treatment is 5-10 hours.

[0030] Furthermore, the composite negative electrode material is obtained by mixing hard carbon and the negative electrode additive by ball milling; preferably, the rotation speed of the ball mill is 400-500 rpm, and the ball milling time is 6-10 h.

[0031] A fourth aspect of the present invention provides a secondary battery comprising the composite negative electrode material described in the third aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention provides a negative electrode additive, which is obtained by in-situ polymerization of a conductive polymer monomer in a solution containing an organic sodium salt. The negative electrode additive comprises an organic sodium salt core and a chain polymer shell, so that the prepared negative electrode additive has high conductivity and is rich in sodium ions.

[0034] 2. The present invention also provides a composite negative electrode material, which is prepared by mixing the above-mentioned negative electrode additive with hard carbon by ball milling. The negative electrode additive dispersed on the surface of the hard carbon particles can not only effectively improve the electronic conductivity of the hard carbon, but also the negative electrode additive rich in sodium ions can compensate for the Na+ in the formation process of the negative electrode SEI film. + The loss of hard carbon can be reduced, thereby improving the capacity and initial coulombic efficiency of the battery. At the same time, the negative electrode additive can act as a protective layer to reduce the side reaction between hard carbon and electrolyte and reduce irreversible capacity. In addition, the high molecular polymer layer on the surface of the negative electrode additive helps to form a uniform and stable SEI film on the surface of the negative electrode, thereby improving the cycle stability of the battery.

[0035] 3. The sodium ion battery constructed with the above-mentioned composite negative electrode material as the negative electrode active material exhibits high capacity, high Coulomb efficiency and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a cycle performance test diagram of Example 1 and the comparative example. DETAILED DESCRIPTION

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."

[0038] As described in the background technology, the internal crystal arrangement of hard carbon is disordered and the interlayer distance is large, which provides space for storing a large amount of charge. However, this disordered structure will cause it to consume a large amount of active sodium during the charging and discharging process, forming a SEI film that causes irreversible consumption, resulting in low initial coulombic efficiency (ICE) and poor cycle stability. At the same time, the poor electrical conductivity of hard carbon itself will further limit its rate performance and cycle performance, affecting its commercial application.

[0039] In order to solve the above problems, the present invention provides a method for preparing a negative electrode additive, comprising the following steps:

[0040] (1) adding a conductive polymer monomer and an organic sodium salt into a solvent and mixing them uniformly to obtain a mixture;

[0041] (2) Adding an initiator solution to the mixture prepared in step (1), stirring the mixture, filtering the mixture, and drying the mixture to obtain the negative electrode additive.

[0042] The present invention obtains a negative electrode additive comprising an organic sodium salt core and a chain polymer shell by in-situ polymerization of a conductive polymer monomer in a solution containing an organic sodium salt, and drying the negative electrode additive. The negative electrode additive is rich in sodium ions and has high conductivity. The negative electrode additive is used in a hard carbon negative electrode. On the one hand, it can improve the electronic conductivity of the hard carbon, and the negative electrode additive rich in sodium ions can compensate for the Na+ in the formation process of the negative electrode SEI film by releasing sodium ions. + The loss of hard carbon can be reduced, thereby improving the battery capacity and the first coulombic efficiency; at the same time, the presence of the polymer shell can achieve the sustained release of sodium ions from the organic sodium salt, which is beneficial to improving the cycle stability of the battery, and the polymer layer on the surface of the negative electrode additive helps to form a uniform and stable SEI film on the negative electrode surface, which can further improve the battery cycle stability. In addition, the negative electrode additive dispersed on the surface of the hard carbon can serve as a protective layer to reduce the side reactions between the hard carbon and the electrolyte and reduce the irreversible capacity. By introducing the negative electrode additive into the hard carbon negative electrode, the battery capacity, first coulombic efficiency and cycle stability can be effectively improved.

[0043] In the present invention, the conductive polymer monomer in step (1) is preferably aniline, pyrrole or thiophene. The polymer formed by polymerizing such monomers has intrinsic conductivity.

[0044] In the present invention, the organic sodium salt in step (1) can be selected from one or more of disodium hexamethylenediaminetetraacetic acid, disodium glutarate, sodium benzoate, and disodium phthalate; such organic sodium salt can be prepared by ion exchange between an organic substance having a carboxyl group and a water-soluble sodium-containing compound, wherein the organic substance having a carboxyl group includes but is not limited to hexamethylenediaminetetraacetic acid, glutaric acid, benzoic acid, phthalic acid, etc., and the water-soluble sodium-containing compound includes but is not limited to sodium carbonate, sodium oxalate, sodium chloride, sodium sulfate, etc.

[0045] In the present invention, the solvent in step (1) can be selected from one or more of water, ethanol, ethylene glycol, N-methylpyrrolidone, dimethylformamide, and toluene to dissolve the conductive polymer monomer.

[0046] In the present invention, in step (1), the organic sodium salt in the mixture is preferably in a supersaturated state, so that the conductive polymer monomer can be polymerized in situ on the surface of the granular organic sodium salt.

[0047] In the present invention, in step (1), the mass ratio of the conductive polymer monomer to the organic sodium salt is (1-3):1, such as 1:1, 2:1, 3:1, etc., including but not limited to the mass ratios listed above.

[0048] In the present invention, the initiator solution in step (2) is obtained by dissolving an initiator in a solvent. Preferably, the initiator is ammonium persulfate and the solvent contains water.

[0049] In the present invention, in step (2), in order to make the conductive polymer monomer fully have, the ratio of the molar amount of the conductive polymer monomer in the mixture to the molar amount of the initiator in the initiator solution is preferably 1: (1-4), such as 1: 1, 1: 2, 1: 3, 1: 4, etc., including but not limited to the ratios listed above.

[0050] In the present invention, in step (2), the initiator solution is preferably added dropwise to the mixture, and during the dropping process: the temperature is preferably -15-5°C, and the dropping time is preferably 1-24h.

[0051] In the present invention, the stirring time in step (2) is preferably 2-4 h, such as 2 h, 3 h, 4 h, etc.

[0052] In the present invention, the drying temperature in step (2) is preferably 80-100° C., and the drying time is preferably 4-5 h.

[0053] In the present invention, the preparation method further comprises the step of washing the filtered product; the washing solvent is preferably ethanol and / or water to remove the uncoated organic sodium salt and prevent the organic sodium salt from affecting the conductivity of the negative electrode additive.

[0054] The embodiments of the present invention also provide a composite negative electrode material, comprising the negative electrode additive prepared by the above preparation method and hard carbon.

[0055] In some preferred embodiments of the present invention, the hard carbon is prepared by the following preparation method, which specifically comprises the following steps:

[0056] S1, calcining the carbon source for the first time under a protective atmosphere to obtain a carbon precursor;

[0057] S2, calcining the carbon precursor for a second time in the presence of a gas phase pore forming agent, and then calcining the carbon precursor for a third time in a protective atmosphere, and then acid washing and drying the product to obtain the hard carbon.

[0058] Preferably, the carbon source in S1 can be selected from one or more of polymer materials, coal materials and biomass materials, wherein the polymer materials include phenolic resin, polytetrafluoroethylene, epoxy resin, furan resin, etc., the coal materials include anthracite, bituminous coal, lignite, coal tar, etc., and the biomass materials include sucrose, glucose, starch, coconut shell, sugarcane, poplar, etc.

[0059] Preferably, the protective atmosphere in S1 and S2 includes one or more of nitrogen, argon, helium and krypton.

[0060] Preferably, in S1, the temperature of the first calcination treatment is 450-550°C, and the time of the first calcination treatment is 3-5h.

[0061] Preferably, in S2, the gas-phase pore-forming agent includes one or more of carbon dioxide, oxygen, air, and water vapor; the gas-phase pore-forming agent is introduced during the heat preservation stage of the second calcination treatment, and the gas flow rate of the gas-phase pore-forming agent is preferably 10-100 L / min.

[0062] Preferably, in S2, the temperature of the second calcination treatment is 800-900°C, and the time of the second calcination treatment is 1-10h; the temperature of the third calcination treatment is 1100-1500°C, and the time of the third calcination treatment is 5-10h.

[0063] In the present invention, the composite negative electrode material is obtained by mixing hard carbon and negative electrode additives through ball milling. Preferably, the ball milling speed is 400-500 rpm and the ball milling time is 6-10 hours, so that the negative electrode additives are evenly dispersed on the surface of the hard carbon.

[0064] The embodiments of the present invention also provide a secondary battery comprising the composite negative electrode material, which exhibits high capacity, high coulombic efficiency and excellent cycle stability.

[0065] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0066] Example 1

[0067] This embodiment relates to the preparation of a negative electrode additive and a composite negative electrode material, and the specific operations are as follows:

[0068] Preparation of negative electrode additives:

[0069] (1) adding water to phthalic acid containing a carboxyl group and stirring for 2 hours until dissolved, then adding sodium carbonate to the solution at a mass ratio of 1:1 to phthalic acid, heating at 100° C. and vigorously stirring for 3 hours to complete ion exchange, filtering, washing with deionized water, and drying to obtain sodium phthalate;

[0070] (2) adding sodium phthalate to NMP solvent and ultrasonically stirring to obtain an organic sodium salt dispersion, adding aniline monomer to the dispersion and stirring to obtain a uniformly dispersed mixed solution (the mass ratio of aniline monomer to sodium phthalate is 2:1);

[0071] (3) Add ammonium persulfate (the molar ratio of aniline monomer to ammonium persulfate is 1:2) to the mixed solution, stir for 2 hours, and in situ polymerize on the surface of sodium phthalate to form a highly conductive polymer. Filter and separate the solid, wash it with water and ethanol several times, put it into a vacuum drying oven at 80°C and dry it for 4 hours. Take it out to obtain a negative electrode additive.

[0072] Preparation of composite negative electrode materials:

[0073] (1) placing starch in a box furnace and carbonizing it at 500° C. for 3 h under argon atmosphere protection, cooling the carbonized product to room temperature, and then crushing the carbonized product to a median particle size of about 8.0 μm by air flow milling to obtain a carbon precursor;

[0074] (2) Subsequently, the carbon precursor is placed in an activation furnace and heated to 900°C in an argon atmosphere, and then carbon dioxide gas is introduced at a flux of 50 L / min, and the temperature is kept for 2 hours for activation treatment. After the activation treatment is completed, it is cooled to obtain an activated product; the activated product is placed in a box furnace, and then heated to 1400°C in an argon atmosphere for treatment for 5 hours. After being taken out, it is pickled with hydrochloric acid and then washed with water until neutral, and after drying, it is sieved with a 325-mesh screen to obtain a hard carbon material;

[0075] (3) The hard carbon material and the negative electrode additive were mixed in a mass ratio of 3:1, and ball-milled on a ball mill at 400 rpm for 8 h to uniformly mix them, thereby preparing a composite negative electrode material.

[0076] Example 2

[0077] This embodiment relates to the preparation of a negative electrode additive and a composite negative electrode material, and the only difference from Embodiment 1 is that an equal mass of pyrrole is used to replace the aniline in Embodiment 1, and the other operations are the same to obtain the corresponding negative electrode additive and composite negative electrode material.

[0078] Example 3

[0079] This embodiment relates to the preparation of a negative electrode additive and a composite negative electrode material, and the only difference from Embodiment 1 is that an equal mass of thiophene is used to replace the aniline in Embodiment 1, and the other operations are the same to obtain the corresponding negative electrode additive and composite negative electrode material.

[0080] Example 4

[0081] This embodiment relates to the preparation of a negative electrode additive and a composite negative electrode material. The only difference from Example 1 is that the mass ratio of the hard carbon material to the negative electrode additive is 4:1, and the other operations are the same to obtain the corresponding negative electrode additive and the composite negative electrode material.

[0082] Example 5

[0083] This embodiment relates to the preparation of a negative electrode additive and a composite negative electrode material. The only difference from Embodiment 1 is that the mass ratio of the hard carbon material to the negative electrode additive is 5:1, and the other operations are the same to obtain the corresponding negative electrode additive and the composite negative electrode material.

[0084] Comparative Example 1

[0085] This comparative example involves the preparation of a hard carbon material, and the specific operation is consistent with the preparation of the hard carbon material in Example 1.

[0086] Comparative Example 2

[0087] This embodiment relates to the preparation of a negative electrode additive and a composite negative electrode material, and is different from Embodiment 1 in that:

[0088] Only sodium phthalate was prepared as the negative electrode additive. Sodium phthalate was mixed with the hard carbon material prepared in Example 1 in a mass ratio of 1:3, and ball-milled on a ball mill at 400 rpm for 8 h to make them uniformly mixed, thereby preparing a composite negative electrode material.

[0089] Comparative Example 3

[0090] This comparative example involves the preparation of a negative electrode additive and a composite negative electrode material, which is different from Example 1 in that the negative electrode additive is directly obtained by mixing polyaniline and sodium phthalate in a solid phase, and the rest is the same to obtain a corresponding composite negative electrode material.

[0091] Application and performance testing

[0092] The composite negative electrode material or hard carbon prepared in the above examples and comparative examples is used as the negative electrode active material to construct a sodium ion half-cell, and the specific operation is as follows:

[0093] Assembly of the sodium-ion half-cell:

[0094] The composite negative electrode material prepared above was mixed with conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) at a mass ratio of 95:1:1.5:2.5, and an appropriate amount of water was added and stirred to obtain a negative electrode slurry, which was applied on a copper foil, and the coated electrode was placed in a vacuum drying oven at 80°C for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon gas, the electrolyte was 1 mol NaPF6-EC / DEC (volume ratio 1:1) + 5% FEC, the metal sodium sheet was the counter electrode, and CR2032 button batteries were assembled in the glove box.

[0095] The sodium ion half-cell constructed with the above different negative electrode active materials was subjected to charge and discharge tests. The test process is as follows:

[0096] First charge capacity and first discharge capacity test: 1) Stand for 2 hours @ (25 ± 2) ℃; 2) Discharge at 0.05C constant current to 0V, stand for 5 minutes, and then discharge at 20μA constant current to 0V to obtain the first discharge capacity; 3) Stand for 5 minutes; 4) Charge at 0.05C constant current to 2.0V to obtain the first charge capacity; 5) Stand for 5 minutes.

[0097] First coulombic efficiency (ICE) = first charge capacity / first discharge capacity;

[0098] Cycle performance test: The sodium ion half-cell was allowed to stand at 25°C for 30 minutes, charged to 2V at 0.05C constant current, allowed to stand for 5 minutes, then discharged to 0V at 0.05C constant current, and then discharged to 0.02C at a constant voltage of 0V. The discharge capacity at this time was recorded as the discharge capacity of the first cycle. The cell was allowed to stand for 10 minutes, and cyclic charge and discharge were performed. The discharge capacity of the sodium ion half-cell at the 500th cycle was recorded as the discharge capacity of the 500th cycle. The capacity retention rate of the 500th cycle = discharge capacity of the 500th cycle / discharge capacity of the 1st cycle.

[0099] The test results are shown in Table 1 below:

[0100] Table 1

[0101]

[0102] As shown in Table 1, compared with Comparative Examples 1 and 2, the negative electrode composite materials prepared in Examples 1, 2 and 3 have higher capacity and first coulomb efficiency, indicating that the addition of the negative electrode additive as a sodium source compensates for the Na +While reducing the loss, the battery conductivity can be further improved, and the battery cycle retention rate is also significantly improved after 500 cycles of charge and discharge. This is because the negative electrode additive can not only replenish the sodium loss caused by the formation of the SEI film by slowly releasing sodium ions, but the high molecular polymer layer on the surface of the negative electrode additive is conducive to the formation of a uniform and stable SEI film, thereby further improving the battery's cycle performance.

[0103] It can be seen from Examples 1, 4, and 5 that as the content of the negative electrode additive decreases, the first efficiency of the battery gradually decreases, which further confirms that the addition of the negative electrode additive is beneficial to the improvement of the capacity and the first efficiency.

[0104] In addition, it can be seen from Example 1 and Comparative Example 3 that directly mixing polyaniline and sodium phthalate solid phases evenly and then adding them to the negative electrode plate as a negative electrode additive has limited effect on improving the first coulombic efficiency of the battery, and the cycle performance of the battery is deteriorated. It is speculated that this is because the organic sodium salt dispersed in the negative electrode affects the conductivity of the negative electrode and the stability of the SEI film, deteriorating the battery impedance and interface stability, thereby causing the battery cycle performance to deteriorate; the core-shell structured negative electrode additive provided by the present invention can effectively improve the first efficiency and cycle performance of the battery.

[0105] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are all within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a negative electrode additive, characterized in that: The following steps are involved: (1) adding a conductive polymer monomer and an organic sodium salt into a solvent and mixing them uniformly to obtain a mixture; (2) Adding an initiator solution to the mixture prepared in step (1), stirring the mixture, filtering the mixture, and drying the mixture to obtain the negative electrode additive.

2. The preparation method according to claim 1, characterized in that: In step (1), the conductive polymer monomer is aniline, pyrrole or thiophene; The organic sodium salt is selected from one or more of disodium hexamethylenetetraacetic acid, disodium glutarate, sodium benzoate, and disodium phthalate; The solvent is selected from one or more of water, ethanol, ethylene glycol, N-methylpyrrolidone, dimethylformamide and toluene.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the conductive polymer monomer to the organic sodium salt is (1-3):

1.

4. The preparation method according to claim 1, characterized in that: In step (2), the initiator solution is obtained by dissolving an initiator in a solvent; preferably, the initiator is ammonium persulfate, and the solvent contains water.

5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the ratio of the molar amount of the conductive polymer monomer in the mixture to the molar amount of the initiator in the initiator solution is 1:(1-4).

6. The preparation method according to claim 1, characterized in that: In step (2), at least one of the following features is included: (1) the initiator solution is added dropwise to the mixture, during which the temperature is -15-5°C and the adding time is 1-24h; (2) The stirring time is 2-4 hours; (3) The drying temperature is 80-100° C. and the drying time is 4-5 hours; (4) The preparation method further comprises the step of washing the filtered product; the washing solvent is ethanol and / or water.

7. A negative electrode additive, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.

8. A composite negative electrode material, characterized in that: Contains hard carbon and the negative electrode additive according to claim 7.

9. The composite negative electrode material according to claim 8, characterized in that: The composite negative electrode material is obtained by mixing hard carbon and the negative electrode additive through ball milling; the rotation speed of the ball mill is 400-500 rpm, and the ball milling time is 6-10 hours; The mass ratio of the negative electrode additive to the hard carbon in the composite negative electrode material is 1:(3-5).

10. A secondary battery, characterized in that: Contains the composite negative electrode material according to claim 8 or 9.

Citation Information

Patent Citations

  • Core-shell structure catalyst for fuel cells and its pulse electrodeposition preparation method

    CN103638925A

  • Positive pole piece and preparation method thereof, electrochemical energy storage device and pre-metallization method of electrochemical energy storage device

    CN112885985A

  • Sodium-based dual-ion battery and preparation method thereof

    CN114430061A

  • Composite lithium supplement agent and preparation method and application thereof

    CN115425304A

  • Sodium ion composite positive electrode material and preparation method and application thereof

    CN115642237A